2010
DOI: 10.1136/jmg.2010.081455
|View full text |Cite
|
Sign up to set email alerts
|

A novel NGF mutation clarifies the molecular mechanism and extends the phenotypic spectrum of the HSAN5 neuropathy

Abstract: BackgroundNerve growth factor β (NGFβ) and tyrosine kinase receptor type A (TRKA) are a well studied neurotrophin/receptor duo involved in neuronal survival and differentiation. The only previously reported hereditary sensory neuropathy caused by an NGF mutation, c.661C>T (HSAN5), and the pathology caused by biallelic mutations in the TRKA gene (NTRK1) (HSAN4), share only some clinical features. A consanguineous Arab family, where five of the six children were completely unable to perceive pain, were mentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
94
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 24 publications
1
94
0
2
Order By: Relevance
“…Probably, the HSAN5 phenotype is extended to encompass HSAN4-like characteristics, so either phenotypes could be parts of a phenotypic spectrum caused by changes in the nerve growth factor/TRKA signalling pathway. Moreover, both expresses identical peripheral nerve biopsy findings 16 . These phenotypes are so rare and well distinguishable by other hereditary sensory neuropathies like Familial dysautonomia or Riley-Day syndrome, which is an neurodevelopmental genetic autosomal recessive disorder, characterized by severe autonomic features including dysphagia, vomiting crises, blood pressure lability, sudomotor dysfunction, poor temperature, motor incoordination.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Probably, the HSAN5 phenotype is extended to encompass HSAN4-like characteristics, so either phenotypes could be parts of a phenotypic spectrum caused by changes in the nerve growth factor/TRKA signalling pathway. Moreover, both expresses identical peripheral nerve biopsy findings 16 . These phenotypes are so rare and well distinguishable by other hereditary sensory neuropathies like Familial dysautonomia or Riley-Day syndrome, which is an neurodevelopmental genetic autosomal recessive disorder, characterized by severe autonomic features including dysphagia, vomiting crises, blood pressure lability, sudomotor dysfunction, poor temperature, motor incoordination.…”
Section: Discussionmentioning
confidence: 92%
“…A specific mutation in the NGF gene causes loss of pain perception and the HSAN5 phenotype. Carvalho et al 16 reported a family where five affected children had a congenital inability to feel pain, anhidrosis, defective temperature sensing, mild intellectual disability, and an immune deficiency, whereas other authors reported a family with a homozygous nerve growth factor mutation presented with congenital lack of pain appreciation, deficient temperature sensing and a lack of C-fibres, but normal sweating, immunity and cognitive abilities 17 . Probably, the HSAN5 phenotype is extended to encompass HSAN4-like characteristics, so either phenotypes could be parts of a phenotypic spectrum caused by changes in the nerve growth factor/TRKA signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation involves a basic arginine (CGG) to a nonpolar tryptophan (TGG) substitution at position 221 in the NGFB amino acid sequence. Rat cell line models suggest that this missense point mutation affects the cleavage of pro-NGF and that the resulting intracellular accumulation of pro-NGF limits the availability of mature NGF in the extracellular space (Carvalho et al 2011;Larsson et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…It does not affect large myelinated A␤-fibers , which are typically negative for the primary NGF receptor TrkA in the cell bodies (Patapoutian and Reichardt 2001). Rat cell line models suggest that this missense point mutation affects the cleavage of pro-NGF, limiting the availability of functional mature NGF in the extracellular space (Carvalho et al 2011;Larsson et al 2009). The R221W mutation carriers' reduced nociceptive afferent density may thus be a consequence of insufficient trophic support from NGF during development, with possible additional effects of altered regulatory signaling in NGF-mediated nociceptive and inflammatory pathways in adulthood.…”
mentioning
confidence: 99%
“…4 It is caused by mutation in NTRK1 gene located on chromosome 1 coding for nerve growth factor B (NGFB) gene. 4,5 Self-mutilation is invariable feature of this disorder most often involving the teeth, lips, tongue, ears, eyes, nose and fingers.…”
Section: Discussionmentioning
confidence: 99%